2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--35144
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Graded Homework Assignments in Statics

Abstract: His return to academia in 2018 resulted from a desire to give back and share his experiences. Particular areas of expertise include constitutive modeling for mechanical behavior of materials, consumer product development, and touch fasteners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…As for those who argue otherwise, it is possible because during the covid-19 pandemic all assignments are not performed in the classroom physically but must be packaged in soft files and uploaded in virtual storage. So the teacher's difficulty is not on the content of the practical assignment but on the ability to package assignments in electronic media and upload them in virtual storage [9].…”
mentioning
confidence: 99%
“…As for those who argue otherwise, it is possible because during the covid-19 pandemic all assignments are not performed in the classroom physically but must be packaged in soft files and uploaded in virtual storage. So the teacher's difficulty is not on the content of the practical assignment but on the ability to package assignments in electronic media and upload them in virtual storage [9].…”
mentioning
confidence: 99%
“…Several studies have investigated how, and even if, homework is graded and the findings are generally that there is no statistically significant difference between these different grading modalities for homework [6], [8], [9]. The biggest impact seems to be getting students to do the work [4], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated how, and even if, homework is graded and the findings are generally that there is no statistically significant difference between these different grading modalities for homework [6], [8], [9]. The biggest impact seems to be getting students to do the work [4], [8], [9]. For example, Lura et al [10] and Fernandez et al [11] found that there was no statistically significant correlation between graded homework and exam performance.…”
Section: Introductionmentioning
confidence: 99%